Interictal regional polyspikes in noninvasive EEG suggest cortical dysplasia as etiology of focal epilepsies - MİDİ, İPEK (WILEY, 2008)
Purpose: To evaluate the clinical significance of interictal regional polyspikes in focal epilepsies secondary to cortical dysplasia. Methods: We performed a data search for the term regional polyspikes in the database of our epilepsy-monitoring unit. Patients with generalized epilepsies including Lennox-Gastaut syndrome were excluded. Regional interictal epileptiform discharges were recorded in 513 patients with noninvasive EEG. Results: We identified 29 patients with interictal regional polyspikes and focal epilepsies. Another 484 patients showed regional epileptiform discharges other than polyspikes. The etiology of the epilepsy was significantly more frequently cortical dysplasia in the group of patients with regional polyspikes (35%, 10 of 29 patients) than in the patients with other regional epileptiform discharges (5%, 24 of 484 patients) (p < 0.01). The polyspikes were significantly more frequently localized to the extratemporal (72%; n = 21) than temporal (28%; n = 8) regions (p < 0.01). In contrast, regional epileptiform discharges other than polyspikes were significantly more frequently localized to the temporal lobe (75%; n = 362) than extratemporal regions (25%; n = 122) (p < 0.01). Eight of the 10 patients with focal cortical dysplasia had extratemporal polyspikes. Discussion: Noninvasively recorded regional polyspikes suggest cortical dysplasias as etiology of predominantly extratemporal epilepsies.
Keywords: EEG; cortical dysplasia; regional polyspikes; epilepsy monitoring; EPILEPTIFORM DISCHARGES; SCALP EEG; MALFORMATIONS; PATTERNS; FEATURES; CHILDREN; SURGERY; PATIENT